Performance evaluating of rural ICT centers (telecenters), applying fuzzy AHP, SAW-G and TOPSIS Grey, a case study in Iran - Zolfani, Sarfaraz Hashemkhani; Sedaghat, Maedeh; Zavadskas, Edmundas Kazimieras (Technological and Economic Development of Economy, 2012)
The project of developing technology in villages was an important project in Iran which was finished in 2010 but it's still being pursued to develop its related services. This project includes many major and minor objectives. After passing six years from the beginning of this project, it seems reasonable to do research about evaluating the progress of these centers. Hence, a framework of evaluation is presented studying past researches utilizing the following criteria; public training, classic training, special training, cultural services, social services, governmental services and other services. Three MCDM methods are applied for evaluating; Fuzzy AHP is used for calculating weights of each criteria and sub-criteria and SAW-G and TOPSIS Grey are applied for evaluating alternatives. Three rural ICT centers are selected as a case study which are located in Golestan Province in north of Iran. The findings show that due to new services presented in these areas, public training and cultural services are more important criteria. Results of SAW-G and TOPSIS Grey are the same which both selected Gharnabad ICT center as the best center and Livan and Bala Jadeh centers are placed as the second and third, respectively.